Réponses

2014-01-02T23:58:49+01:00
A) 3x + 2 = 0
3x = -2
x = -2/3
b) - 7 x - 5 =0
- 7 x = 5
x = - 5/7
c) 18 x = 0
x = 0
d) 1/2 x - 7 = 0
1/2 x = 7
x = 7 * 2
x = 14
e) - 3/7x + 4/5 = 0
- 3 /7 x = - 4/5
x = - 4/5 *  -7/3
x = 28/15
f) 3 (x-2) - 7(x+1) =0


f) 3x - 6 - 7x - 7 = 0
- 4 x - 13 = 0 x = - 13/4
g) (x+1)² - 4x = (x-1)² (x+1)² - (x-1)² - 4x =0 (x+1+x+1) (x+1-x+1) -4 x = 0 (2x +2) *2 - 4x =0 Impossible car 4 n'égale pas 0
h) 3/5 * (1-2x) -1/5 * (2+9x) = 1/5 -3x 3/5 - 6/5 x - 2/5 - 9/5 x -1/5 + 15/5 x=0 et donne 0=0
Dans le h, y'as un signe entre "3x et 3/5" ??